The effect of problem-based learning model assisted by independent learning activity units on numeracy literacy skill of grade X MA students - Asruri, Selfi; Maysarah, Siti (Desimal: Jurnal Matematika, 2025)
For students, numeracy literacy skills are very important for understanding and exploring quantitative relationships in real-world contexts. Low numeracy literacy skills among students are caused by teacher-centered learning. This study aims to determine the effect of the problem-based learning model assisted by Independent Learning Activity Units on the numeracy literacy skills of 10th grade MA students. The quantitative methodology used in this study is a quasi-experimental design employing a post-test-only control group design. The sample consists of 60 students divided into an experimental group and a control group, selected through purposive sampling from the population of X-grade students at MAN Serdang Bedagai. Sampling was conducted using purposive sampling, with the condition that both groups have a normal distribution and are homogeneous. This study used a numeracy literacy test instrument that has been proven to be valid and reliable. Data analysis techniques used the independent sample t-test. The conclusion that the use of the Problem-Based Learning model assisted by Independent Learning Activities units significantly influenced the numeracy literacy skills of grade X students at MA. Students taught using the Problem-Based Learning model assisted by Independent Learning Activity Units have been proven to be effective in improving students' numeracy literacy, particularly in the aspects of analysis, data interpretation, critical thinking, and problem solving, compared to students taught using conventional methods.